Desarrollo de un sistema de registro automático del tiempo de pastoreo en rumiantes - Raggi Saini, Luis Alberto; Crossley Cabezón, Jorge Ernesto; Sepúlveda Luque, María Soledad; Jiliberto Fritis, Eduardo Andrés (Monografías de Medicina Veterinaria, 1990)
-